Outcomes of CCAFS Work in Vietnam - Ferrer, Alice Joan G; Bernardo, Eisen Bernard (2020)
The study explored how CCAFS SEA outputs have helped the country achieve its development outcomes in the agricultural sector. The assessment showed that CCAFS SEA, although still on-going, has contributed to specific outcomes in Vietnam, which include changes in knowledge, approaches, practices, and strategies related to climate change, particularly in the agricultural sector. These outcomes were observed among decision makers, policymakers, technical staff, and farmers.